Epistemic logic : a survey of the logic of knowledge - Rescher, Nicholas (Pittsburgh, Pa. : University of Pittsburgh Press, 2005)
"Epistemic Logic examines the nature of knowledge, the conceptual ramifications of defining knowledge, and the reach and limits of what we know. As the branch of philosophy that formalizes the discourse on knowledge, epistemic logic seeks to articulate and clarify the general principles of reasoning about knowledge. Nicholas Rescher gives an overview of the discipline by setting out the general principles for reasoning about such matters as propositional knowledge and interrogative knowledge. Aimed at graduate students and specialists, it elucidates both Rescher's pragmatic view of knowledge and the field in general."--Jacket
1. Setting the stage -- 2. Basic principles -- 3. Deductivity and knowledge ampliation -- 4. Metaknowledge -- 5. For aught that someone knows -- 6. Group knowledge -- 7. Propositional versus interrogative knowledge -- 8. Collective versus distributive knowledge and knower limitedness -- 9. Modality -- 10. Problems of epistemic democracy -- 11. Possibility and conceivability -- 12. Unknowability -- 13. Fitch's theorem and its consequences -- 14. Finite and infinite knowers -- 15. Vagrant predicates and noninstantiability -- 16. Unanswerable questions and insolubilia -- 17. Unknowable truth -- 18. Implications of cognitive limitation -- App. 1. A survey of thesis acceptability
Includes bibliographical references (pages 135-138) and index
Keywords: Epistemics; Logic; Knowledge, Theory of